Observing the Near‐Surface Properties of the Greenland Ice Sheet. Issue 8 (26th April 2023) - Scanlan, K. M.; Rutishauser, A.; Simonsen, S. B.
Abstract: Spaceborne radar altimetry over ice sheets has exclusively focused on assessing volume changes through changes in surface elevation. For use in mass balance calculations, these measurements are supplemented with surface property information derived from regional climate models with limited large‐scale observational validation. Simultaneously, the strength at which a radar signal is reflected from the surface contains information on these same near‐surface properties. Here we show that a quantitative interpretation of European (ESA) CryoSat‐2 and French/Indian (CNES/ISRO) SARAL surface echo powers yields timeseries of pan‐Greenland wavelength‐scale roughness and surface density. Individually, the CryoSat‐2 and SARAL results strive toward providing an observational lens to enhance our current understanding of the surface processes affecting ice sheet mass balance and validate their representation by computational models. Taken together, they highlight how diversity in currently operational and future radar satellite altimetry missions can shed light on near‐surface vertical heterogeneity. Plain Language Summary: For three decades, satellite‐based radar altimeters have been measuring areas of thickening and thinning across the Greenland ice sheet (GrIS). From these measurements we can calculate a mass balance, which is an important component in quantifying Greenland's contribution to global mean sea level rise. However, this calculation requires knowing ice sheet surface density. Even though predictable with specialized computer programs, observations are needed to ensure the computer results are accurate. In this study, we use three different radar data sets from two different satellites, to measure the surface density and roughness of the GrIS based on the strength of the radar altimetry surface echoes. As expected, surface roughness increases toward the ice sheet margin and in the vicinity of faster flowing ice. Surface density varies through time and space but appears strongly influenced by melt events (e.g., summer 2012). By comparing measurements between satellites, we can start piecing together how density changes vertically in the near surface; reflecting the processes operating at the time (i.e., snow fall, melting, melt percolation). These observations are the first step toward providing a new data set for refining the computer programs used to project Greenland evolution into the future. Key Points: In‐depth knowledge of near‐surface density is crucial for altimetry ice sheet mass balance estimates We provide the first, monthly, pan‐Greenland observations of surface roughness and density between 2013 and 2018 Dual‐frequency results reflect deposition, melting, and percolation processes through their influence on vertical density heterogeneity